2013
DOI: 10.4414/smw.2013.13730
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study on the quality of oral anticoagulation therapy in chronic haemodialysis patients treated with phenprocoumon

Abstract: In our ESRD cohort, the percentage of INR in target range in patients treated with phenprocoumon seems comparable with published data on warfarin and data in non-ESRD populations. However, this finding has to be confirmed in larger studies powered for analysing the factors influencing INR control and the impact of INR control on bleeding and thromboembolic events in ESRD patients treated with phenprocoumon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Conversely, two studies suggested that warfarin use may not significantly increase the risk of bleeding . Nephrologists are therefore faced with concerns about the risk—benefit assessment before prescribing oral anticoagulants and/or additional anticoagulation to prevent clotting during the HD session without additional bleeding complications in such patients .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, two studies suggested that warfarin use may not significantly increase the risk of bleeding . Nephrologists are therefore faced with concerns about the risk—benefit assessment before prescribing oral anticoagulants and/or additional anticoagulation to prevent clotting during the HD session without additional bleeding complications in such patients .…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, the incidence of major hemorrhage for hemodialysis patients treated with and without warfarin was 10.8 and 8.0/100 patient-years, respectively, compared to 2.1/100 patient-years for patients without renal failure treated with warfarin [22]. Patients with ESRD have also been found in some [17,23] but not all studies [25,26] to spend a greater proportion of time outside the therapeutic INR window than patients from the general population. Patients with severe renal failure have been shown to require a lower dose of warfarin [23], which might be related to a relative vitamin K deficiency [24].…”
Section: Risks and Benefits Of Oral Anticoagulantsmentioning
confidence: 97%
“…In a recent study, Praehause et al [38] analysed the quality of oral phenprocoumon treatment control in ESRD patients, suggested that phenprocoumon is not inferior to warfarin. The phenprocoumon therapeutic effect in HD patients with AF required to further verification.…”
Section: A N U S C R I P Tmentioning
confidence: 98%